A sequential recovery extraction and biological activity of water-soluble sulfated polysaccharides from the polar red macroalgae Sarcopeltis skottsbergii - Castro Varela, Pablo Andrés; Rubilar, Mónica; Rodrigues, Bruna; Pacheco-Rodriguez, María Jesús; Caneda-Santiago, Candela T.; Mari-Beffa, Manuel; López-Figueroa, Félix; Abdala-Díaz, Roberto Teófilo (Elsevier, 2023)
Algal biomass is comprised of a variety of biochemical components that make it a viable raw material for use in a variety of applications using a biorefining process. From the residual supernatant generated by high-pressure homogenization for the extraction of the R-phycoerythrin pigment, two soluble polysaccharides (neutral and acid fractions) were obtained. The composition of total carbon (C), hydrogen (H), nitrogen (N), and sulfur (S), gas chromatography–mass spectrometry (GC–MS), Fourier transform infrared (FTIR-ATR) spectroscopy, antioxidant capacity (ABTS) and antiproliferative in vitro and in vivo activities were evaluated. The two polysaccharides, which had a relatively high sulfate content, exhibited significant antioxidant activity in superoxide radical assay (ABTS) and high anti-proliferative effects on G-361, U-937, HCT-116 cancer cells. High selectivity index (>3) was observed for the acid extract on G-361 and U-937 cell lines, but a significant inhibitory effect on the growth of 1064sK healthy fibroblast cells was measured too. On the other hand, neutral fraction polysaccharides, with the lowest sulfate content and relatively lower radical scavenging rates, showed scarce antitumor activity, a high selectivity index on G-361 melanoma cancer cells and non-toxicity on healthy cells. This differential behavior was verified by testing toxicity and lethality of both polysaccharide extracts in and in vivo zebrafish embryo acute toxicity test. Following this method, the LC50 of the neutral fraction resulted much higher (1.477 mg mL 1, p ≈0.0000) than that of the acid fraction (0.080 mg mL 1, p ≈0.0000) at 72 h post-fertilization. During this period, a slight growth delay and/or rare teratogenic effects were also induced by these fractions at concentrations lower than their LC50.
https://openpolicyfinder.jisc.ac.uk/id/publication/21119
Keywords: Polisacáridos; Rodofíceas; Biomasa - Composición; Peces cebra; Recovery extraction; Sulfated polysaccharides; Antioxidants activity; Antitumor active; Zebrafish; Red seaweed